The positioning behind one`s forerunner in the final stages of the race distinguishes elite and subelite short track speed skaters - de Jong, R.; Konings, M. J.; Al, M.; Hettinga, F. J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Pacing can be seen as a continuous decision-making process related to how and when to invest your energy (Smits et al., 2014). Previous research explored the pacing strategies of short track speed skaters and emphasized the importance of tactical positioning (Konings et al., 2016). In addition, the positioning behind one`s forerunner might be crucial in order to provide oneself the opportunity to overtake the forerunner. The present study explored how elite and sub-elite short track speed skaters positioned themselves behind their forerunner. Methods: Lap times and intermediate positions of 1500m races were collected from short track speed skating World Cups, European and World Championships over the seasons 11/12 until 14/15 (N=7157 individual races). Short track skaters were classified by proficiency: skaters with a top 10 World Cup ranking were classified as elite (ELITE; N=35 athletes, 716 individual races), while skaters with a World Cup ranking between 20-30th place were classified as sub-elite (SUB; N=34 athletes, 392 individual races). The positioning behind one`s forerunner was determined by calculating the time the forerunner preceded the participant in every lap. Differences between elite and sub-elite riders in the positioning behind one`s forerunner were determined using independent t-tests (p<0.05). Results: SUB positioned themselves closer behind their forerunner in the first three laps compared to ELITE (Lap 1: SUB=0.13±0.07 sec vs. ELITE=0.15±0.08 sec, P=0.001; Lap 2: SUB=0.13±0.06 sec vs. ELITE=0.14±0.08 sec, P=0.021; LAP 3: SUB=0.12±0.05 sec vs. ELITE=0.13±0.08 sec, P=0.006). In contrast, ELITE positioned themselves closer behind their forerunner in the last four laps (Lap 11: ELITE=0.10±0.07 sec vs. SUB=0.14±0.12 sec, P<0.001; Lap 12: ELITE=0.11±0.09 sec vs. SUB=0.18±0.20 sec, P<0.001; Lap 13: ELITE=0.15±0.15 sec vs. SUB=0.27±0.31 sec, P<0.001; Lap 14: ELITE=0.21±0.31 sec vs. SUB=0.47±0.66 sec, P<0.001). Discussion: Elite short track skaters appeared to be able to position themselves closer behind their forerunner compared to sub-elite skaters during the final, decisive stages of the race. Our findings emphasize the importance of tactical positioning in short track speed skating competitions, and propose the positioning behind one`s forerunner in the final, decisive stages of the race as a distinguishing factor between elite and sub-elite short track speed skaters.